2011
DOI: 10.1111/j.1365-2966.2011.19855.x
|View full text |Cite
|
Sign up to set email alerts
|

The SAURON project - XX. The Spitzer [3.6] − [4.5] colour in early-type galaxies: colours, colour gradients and inverted scaling relations

Abstract: We investigate the [3.6]−[4.5] Spitzer‐IRAC colour behaviour of the early‐type galaxies of the SAURON survey, a representative sample of 48 nearby ellipticals and lenticulars. We investigate how this colour, which is unaffected by dust extinction, can be used to constrain the stellar populations in these galaxies. We find a tight relation between the [3.6]−[4.5] colour and effective velocity dispersion, a good mass indicator in early‐type galaxies: ([3.6]−[4.5])e = (−0.109  0.007)+ (0.154  0.016). Contrary to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 98 publications
3
50
0
Order By: Relevance
“…We additionally explored a more sophisticated way to compute mass-to-light ratios, using the color-3.6 G relation published by Meidt et al (2014), their Equation (4)), which allows one to estimate 3.6 G of a galaxy from its Table 1) when available for our galaxies, or were estimated from the bulge stellar velocity dispersion, σ, using the color-σ relation presented by Peletier et al (2012, their Figure 6). We found that the range in [3.6]-[4.5] color is small (0.06 mag), and thus the range in 3.6 G is also small (0.04).…”
Section: Datamentioning
confidence: 99%
“…We additionally explored a more sophisticated way to compute mass-to-light ratios, using the color-3.6 G relation published by Meidt et al (2014), their Equation (4)), which allows one to estimate 3.6 G of a galaxy from its Table 1) when available for our galaxies, or were estimated from the bulge stellar velocity dispersion, σ, using the color-σ relation presented by Peletier et al (2012, their Figure 6). We found that the range in [3.6]-[4.5] color is small (0.06 mag), and thus the range in 3.6 G is also small (0.04).…”
Section: Datamentioning
confidence: 99%
“…They argue that the model predictions at these wavelengths are much less susceptible to the uncertainties due to the details of the SPS treatment, with the 3.6µm emission dominated by old stars on the red giant branch (e.g. Spitler et al 2008, da Cunha et al 2008, Peletier et al 2012, Röck et al 2015 and that there is much less variation in mass-to-light ratio due to age/SFH and metallicity than seen at shorter wavelengths. They also argue that the treatment of the contribution of AGB stars in the original BC03 models better matches observations than do those in either the more recent 2007 version of BC03, or the alternative prescription in Maraston (2005).…”
Section: Sps Predictions For the Mid-irmentioning
confidence: 99%
“…In particular the 3.6µm band data represents a major asset for our understanding of the stellar population of these galaxies, given the insensitivity of the 3.6µm band images to dust extinction and the fact that they provide a good reflection of the old stellar population in these galaxies (see e.g. Peletier et al (2012) and Meidt et al (2014) for a discussion). This also means that the 3.6µm flux, together with the [3.6]-[4.5] colour provide us with a robust estimate of the stellar mass of a galaxy, since the old stellar population constitutes its major share.…”
Section: Introductionmentioning
confidence: 99%